Thermosolutal convection in a rotating couple-stress uid - Palese, Lidia Rosaria Rita (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we study the nonlinear Lyapunov stability of the conduction-diusion solution of a rotating couple-stress uid, in a layer heated and salted from below. After reformulating the perturbation evolution equations in a suit- able equivalent form, we derive the appropriate Lyapunov function and we prove that, if the principle of exchange of stabilities holds, the linear and nonlinear stability bounds are equal.The nonlinear stability bound is exactly the critical Rayleigh num-ber obtained solving the linear instability problem of the conduction- diusion solution.